Influence of Underground Tunnel Excavation on Upper-level Existing Pipelines - Xingfa Feng; Xian Yang; Yongsuo Li; Xingyu Ding (Advances in Civil Engineering)
Winkler elastic foundation beam theory is often used to observe the influence of underground engineering construction on pipelines. Excavation under existing pipelines disturbs the lower strata to varying extent, which creates significant differences in the subgrade coefficients. Ignoring these differences can severely impact the accuracy of calculation results. A theoretical model of the effects of underground excavation on upper-level existing pipelines was developed in this study based on Winkler elastic foundation beam theory and considering the difference of subgrade coefficients under the existing pipeline. Methods for determining the subgrade coefficient under the influence of construction disturbance and other relevant parameters are proposed. The theoretical model can be used to calculate the settlement of an existing pipeline under the influence of underground excavation. The calculated settlement was compared with settlement measurements to find that the subgrade coefficient of the excavation section is the most important parameter in the calculation process. The suitable value range of the excavation subgrade coefficient is relatively large, as it has a relatively minor influence on the calculation result. When the value of subgrade coefficient of each section is appropriate, the calculated settlement curve is in close accordance with the measured settlement curve.